Structural investigations of superconducting multilayers consisting of semiconducting materials - Erenburg, A. I.; Fogel, N. Ya.; Bomze, Yu. V.; Sipatov, A. Yu.; Fedorenko, A. I.; Langer, V.; Norell, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
There are rather exotic semiconducting superlattices (SL) consisting of monochalcogenides of Pb, Snand rare-earth metals which exhibit superconductivity at temperature as high as 6 K. Here we report theresults of precision x-ray diffractometry and TEM investigations as well as Auger spectroscopy dataobtained on some of the epitaxially grown superconducting semiconducting SLs. It is established thatessential features of the SL structure determining the appearance of superconductivity are the perfect single-crystallinity of the samples and the presence of continuous dense grids of misfit dislocations onthe interfaces between two semiconductors. The segregation of free Pb which was observed in some cases does not correlate, according to experimental data, with the appearance of superconductivity.